A modelling system for air quality management. (1st January 2000) - Borrego, C.; Lemos, S.; Carvalho, A.C.; Coutinho, M.
To develop effective air quality management strategies at regional and urban levels requires the preparation of several actions belonging to different scientific areas and analysis of their complex interactions. A well-structured management system must be based on efficient tools that integrate diverse sets of information - emissions, traffic, meteorological variables and air quality data. Ideally, such a system should include appropriate modelling tools that could be used to perform spatial interpolation and air quality forecasts. This paper will describe the modelling system developed for predicting the emissions (emission pre-processor), dispersion and chemical transformation of pollutants in urban areas and its application for two sites in Portugal (Lisbon and Oporto). For predicting the concentration fields, all categories of sources are taken into account, namely stationary point and area sources and traffic. This allows the construction of an urban air quality management system for decision support.